The SAGE dictionary of qualitative management research - Thorpe, Richard, 1951-; Holt, Robin, 1966- (Los Angeles, Calif. ; London : SAGE, 2008)
With over 100 entries on key concepts and theorists, this dictionary of qualitative management research provides full coverage of the field, explaining fundamental concepts and introducing new and unfamiliar terms.
Includes bibliographical references and index.
Specialized.
Description based on print version record.
Keywords: elektronické knihy; electronic books; Management -- Research -- Dictionaries; Qualitative research -- Dictionaries